Factors considered by the buyer in the selection of telecommunication company - Dalisay, Jessicar B.; Ortigas, Nestor A., Jr.; Palomar, Connie R.; Tabigo-on, Christine G. (2001.)
This study aimed to determine the factors considered by the buyer in the selection of Telecommunications Company in the city of Iloilo. Based on the observations of the researchers, the subscribers preferred SMART and GLOBE Telecom, which gave them interest to study. The researchers took two groups of respondents-the current-users of celfones and the incoming users. Sixty respondents were purposively selected from each group of users. For the current-users, the researchers selected thirty from those who enjoyed the service of GLOBE Telecom and the other thirty was for SMART Telecom. On the other hand, the same number of respondents for those who were planning to subscribe for GLOBE and thirty for SMART. Questionnaire were given to these two groups of respondents. Also, to supplement the data, sets of interview schedules with the key personnel/owner of the said Telecommunications Companies in Iloilo City were conducted. Statistical techniques were also used in the analysis of data. After analyzing the data gathered, the researchers found out that most current-users were greatly influenced by their friends and family members in the selection of Telecom company. It also appeared that current-users chose to subscribe in their present Telecom Company because they wanted to keep in touch with their family, friends and loved ones. These were considered as individual factors. For company factors, current-users considered the availability of network coverage and affordability of rates. Furthermore, using statistical techniques, it appeared that socio-economic factors, marital/civil status and sex have no relation with buying behavior of consumers. However, the researcher found out that age was related to the consumers' buying behavior.
[Research Paper] (BA 200 - Business Research). -- Iloilo City : University of the Philippines in the Visayas - College of Management, March 30, 2001.